حياة يوسف عليه السلام والتخطيط تلاقتصادي في زمانه - منيرة يونس (Kolej Universiti Islam Malaysia, 2022)
The method of this study are library method. By this method most material are found from library. From this method also each book about the topic are being carried out to have a clear picture about governance and also innovation which was done by Yusuf a.s to developing Egypt. The process of ruling and development that had been carried out are suitable during that time. This study also discusses about challenges that happened to Yusuf a.s before hosted as an important person in Egypt. Both material for this study come from various resources such as books about history and also interpretation from the al-Quran. Beside that the material also are carried out from the Internet. And finally, the study concludes that challenges which are faced by Yusuf a.s helped him to be a stronger person; and from the governing aspects the changes that he aced are suitable not just at that time but also can be implemented today.